Modification of Sago Starch and Polyvinyl Alcohol Blends by Irradiation for the Production Of Biodegradable Foams And Foam Trays - Pimpa, Benchamaporn Wongsuban @ Benchamaporn (2007)
Electron beam irradiation induced cross-linking in aqueous PVA and PVP but caused degradation in aqueous sago starch. Sago starch/PVP blends were more readily cross-linked than sago starch/PVA blends. The gel strength of both blends was increased when the irradiation dose was increased due to the cross-linking. Sago starch was found to enhance the gel strength of the blends. An enhancement in storage modulus and tan δ with increment in irradiation dose further indicated the formation of irradiation-induced cross-linking. This confirmed that there was molecular interaction occurring in the sago starch/PVA and sago starch/PVP blends. Grafting might have also occurred in the irradiated sago starch/PVA and sago starch/PVP blends as can be observed from the shifting of the thermogravimetric analysis spectrum. The findings of electron microscopic studies on the fracture surface morphology of the blends gave further evidence on the occurrence of irradiation induced cross-linking in them. The effects of the type and concentration of polymers, mixing temperature and electron beam irradiation dose on properties of foam were investigated. Blends of sago starch/polyvinyl alcohol (PVA) and sago starch/polyvinyl pyrrolidone (PVP) were mixed at 25°C and 80°C. They were then electron beam irradiated with doses ranging from 10 to 30 kGy. Foams were subsequently produced by puffing the irradiated blends in a microwave for 5 to 8 min. High linear expansion foams can be produced from 25:15 of sago starch:PVA, 30:10 of sago starch:PVA, 20:20 of sago starch:PVP and 25:15 of sago starch:PVP blends mixed at 80°C. Irradiation dose of 15 kGy was found to be suitable in the production of the sago starch/PVA foams with maximum linear expansion of the foams obtained while 10 kGy was suitable for the production of the sago starch/PVP foams. An increment of sago starch in the blends enhanced the linear expansion of the foams. Changes in blend morphology were observed when the blends were exposed to higher irradiation doses. Sago starch/PVA blend was suitable for foam production because it produced a flexible and glossy foam as compared to sago starch/PVP blend that produced a very rigid foam. The linear expansion ratio of foam from sago starch/PVA blend was higher than that of foams from tapioca starch/PVA, wheat starch/PVA and corn starch/PVA blends. The irradiated sago starch/PVA blend was moulded into trays by a hot and cold press machine. The physical characteristics of the trays such as tear resistance, water absorption capacity and moisture absorption isotherm were then determined. Irradiation or cross-linking of the sago starch/PVA blend increased the tear and moisture resistances of the foam trays produced from it. Results of the soil burial test showed that the sago starch/PVA foam trays were biodegradable with up to 40% of weight loss occurring in the first month of the burial period. This was accompanied by the growth of microbes, presumably fungi, which were observed on the foam trays under the scanning electron microscope.